Interactive Multimedia Based on the Project-Based Learning (PjBL) Model on the Topic of Light for Grade V - Ni Putu Cindy Pratiwi Putri; Ni Wayan Rati; Ni Nyoman Rediani (Jurnal Media dan Teknologi Pendidikan, 2025)
The low learning outcomes of students in Science learning are often caused by the use of unappealing and non-contextual learning media, as well as learning approaches that do not encourage active engagement through real projects. This study aims to develop and analyze the feasibility and effectiveness of Interactive Multimedia based on the Project Based Learning (PjBL) model in improving elementary school students’ learning outcomes. This research employed a research and development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of four experts, two teachers, and ten fifth-grade students. Data were collected using a closed-ended questionnaire with a rating scale and multiple-choice objective tests, then analyzed descriptively and quantitatively to assess the validity, practicality, and effectiveness of the product. The results showed that the media achieved a very high level of validity with an average expert score of 0.90. The practicality of the media was rated good by teachers with an average score of 3.43 and by students with an average score of 3.33. The media was also proven effective in improving learning outcomes on the topic of Light. The main findings of this study emphasize that integrating the PjBL model into interactive multimedia can create a more active, contextual, and student-centered learning experience. Therefore, the developed PjBL-based Interactive Multimedia is declared valid, practical, and effective for supporting meaningful science learning and has the potential to be widely implemented in elementary education contexts.